2010
DOI: 10.1111/j.1526-4637.2010.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Double-blinded, Placebo-controlled, Prospective Randomized Trial Evaluating the Efficacy of Paravertebral Block with and Without Continuous Paravertebral Block Analgesia in Outpatient Breast Cancer Surgery

Abstract: The current study does not support the routine use of continuous paravertebral catheter anesthesia in patients undergoing operative treatment for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 18 publications
1
40
2
2
Order By: Relevance
“…Relatedly, nonsteroidal antiinflammatory agents, gabapentin, and local anesthetic wound infiltration/infusion were not used per the surgeon's preferred standard analgesic regimen, the addition of which may have decreased the differences found between the two treatment groups. [42][43][44] In addition, although the overwhelming number of investigations, including those of the current study, involving breast surgery and paravertebral infusion included the third thoracic level for catheter insertion, [45][46][47][48][49][50][51][52] the optimal level for mastectomy analgesia remains unknown. We did not measure blood levels of nociceptive processing or stress response markers that could have helped elucidate any association of perioperative analgesia with persistent postoperative pain and cancer recurrence.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Relatedly, nonsteroidal antiinflammatory agents, gabapentin, and local anesthetic wound infiltration/infusion were not used per the surgeon's preferred standard analgesic regimen, the addition of which may have decreased the differences found between the two treatment groups. [42][43][44] In addition, although the overwhelming number of investigations, including those of the current study, involving breast surgery and paravertebral infusion included the third thoracic level for catheter insertion, [45][46][47][48][49][50][51][52] the optimal level for mastectomy analgesia remains unknown. We did not measure blood levels of nociceptive processing or stress response markers that could have helped elucidate any association of perioperative analgesia with persistent postoperative pain and cancer recurrence.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Preincisional PVB reduces chronic pain by incidence and intensity one year following breast cancer surgery, possibly by reducing the intensity of the acute pain several days postoperatively [9]. Our practice is to place the PVB prior to surgery.…”
Section: Discussionmentioning
confidence: 97%
“…A randomized prospective study examined if there was any advantage in placing a PVB with a catheter. The study concluded that a catheter conferred no added benefit [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the ambulatory setting of 'simple breast surgery' a continuous paravertebral infusion in addition to single shot blocks, did not improve pain, nausea, or mood scores or hasten return to normal activity [58]. It appears that the low pain scores of breast conserving surgery (\3 on a 0-10 scale) do not warrant ongoing infusions, and these should be reserved for more invasive surgery, e.g., mastectomy with immediate reconstruction [58].…”
Section: Trunk Surgerymentioning
confidence: 98%
“…It appears that the low pain scores of breast conserving surgery (\3 on a 0-10 scale) do not warrant ongoing infusions, and these should be reserved for more invasive surgery, e.g., mastectomy with immediate reconstruction [58].…”
Section: Trunk Surgerymentioning
confidence: 99%